Early detection of colorectal cancer using a hybrid model with enhanced image quality and optimized classification - Bozdag, Ahmet; Karaduman, Mucahit; Kiziloluk, Soner; Karaduman, Gulsah; Yildirim, Muhammed; Yildirim, Ozal; Acharya, U. Rajendra (Springer, 2025)
Colorectal cancer starts in the large intestine and rectum. It develops when small, usually harmless growths called polyps become cancerous over time. Early diagnosis increases the chances of successfully treating colorectal cancer. A new hybrid model was developed to detect colorectal tissue types. In the first step of the model, the quality of the images was increased using Denoising Convolutional Neural Network (DNCNN) networks. The feature maps of the images were then obtained using DarkNet53 and shrunk using the Gorilla Troops Optimization Algorithm (GTO) to speed up the proposed model's performance and boost the performance. Finally, a support vector machine (SVM) classifier was used to classify the feature maps. The proposed model obtained an accuracy of 95.5% in classifying eight tissue types in colorectal cancer histopathology specimens (Adipose, Complex, Debris, Empty, Lympho, Mucosa, Stroma, and Tumor). To make the developed model more generalizable, robust, and accurate, it needs to be tested with a huge dataset collected from various centers and races.
Keywords: Classifiers; CNN; Colorectal cancer; DNCNN; GTO